Law And Sovereignty - Eleftheriadis, P (2010)
How is it possible that the idea of sovereignty still features in legal and political philosophy? Most contemporary political philosophers have little use for the idea of unlimited or absolute power, which is how sovereignty is normally defined. A closer look at sovereignty identifies two possible accounts: sovereignty as the fact of power or sovereignty as a title to govern. The first option, which was pursued by John Austin s command theory of law, leads to an unfamiliar view of law and the state, which was justly criticised by H. L. A. Hart. The second option, leads to a paradox, because under this view sovereignty is both limited and unlimited. Hence, this argument shows that law and sovereignty are actually incompatible. Where there is law there is no sovereignty, and where there is sovereignty there is no law. © Springer 2010.